ROLE OF MANIPUR CHAKRA ACTIVATION IN TREATMENT OF DIABETES MELLITUS: Array - Dr. yasmeen khan; VINOD CHOUDHARI (Ayurline: International Journal of Research in Indian Medicine, 2021)
Chakras are the circular vortex of energy lying across the seven different points on your spinal column. On a physical level, chakras are associated with the major nerve plexuses and endocrine glands in the body. Many asanas have particularly powerful and beneficial effect on one or more of these glands or plexuses. Chakras are not the physical entity and reside in energy body, but help us to understand the body functions and emotions. As they are psychoactive energy centers in human body they are directly related to physiological and psychological health of human being. The unavoidable stress in lifestyle has blocked the entire chakra system and imbalance in the energy flow causes various diseases. We have the great ancient knowledge with us to regulate the energy flow through chakras and get cured from various disorders related to that chakra. Mechanism of yoga effects is the most visible in the systems of chakras and nadis, which specifically and directly correlates with nervous and endocrine system. This study is a small effort to prove the effect and application of Manipur chakra activation in management of life style disorders especially diabetes mellitus.